2012
DOI: 10.1099/jmm.0.042663-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant clones of community-associated meticillin-resistant Staphylococcus aureus isolated from Chinese children and the resistance genes to clindamycin and mupirocin

Abstract: This study aimed to correlate the multidrug resistance (MDR) and sequence type (ST) clones of community-associated (CA) meticillin-resistant Staphylococcus aureus (MRSA) to identify the genes responsible for clindamycin and mupirocin resistance in S. aureus isolates from paediatric hospitals in mainland China. A total of 435 S. aureus isolates were collected. Compared with CA meticillinsusceptible S. aureus (MSSA), the resistance rates of CA-MRSA to ciprofloxacin, chloramphenicol, gentamicin and tetracycline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
5
29
1
Order By: Relevance
“…Plasmid of 23.4 kb to 50 kb was the most common which accounted for 90.6%. Previously we showed that the position of mup A gene in high level mupirocin resistant MRSA was present in the plasmid of 23.4 kb to 50 kb [52]. Further studies are needed to explain the relationship between antibiotic resistant genes and plasmids.…”
Section: Discussionmentioning
confidence: 95%
“…Plasmid of 23.4 kb to 50 kb was the most common which accounted for 90.6%. Previously we showed that the position of mup A gene in high level mupirocin resistant MRSA was present in the plasmid of 23.4 kb to 50 kb [52]. Further studies are needed to explain the relationship between antibiotic resistant genes and plasmids.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the ST59 isolates had less antibiotic resistance than ST239 and ST5 isolates. Clones harboring SCC mec IV or V and carrying PVL are usually reported in the context of community-onset infections, and ST59 is known to be the most common CA-MRSA clone among Chinese children (Geng et al, 2010; Wang et al, 2012). In Hong Kong and Taiwan, CA-MRSA clones, including ST59, have spread to hospital settings (Song et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Livermore et al recently reported that the susceptibility to chloramphenicol among 20 carbapenemase-producing Enterobacter strains was only 20% [7]. According to this observation, we could speculate that the Enterobacter phenotype is similar to that of K. pneumoniae, where resistance to [60] 2009 Pakistan 501 KB 90 [61] 2010 Pakistan 139 KB 93 [62] 2010 India 69 KB 60 [63] 2010 USA 21 MicroScan 91 [64] 2010 Pakistan 174 KB; E-test 7 [65] 2011 Greece 44 KB 70 [66] 2011 USA 170 -96 [67] 2011 Canada 51 Sensititre 98 [68] 2011 Iran 140 KB 100 [69] 2011 Libya 62 KB 61 [70] 2011 Nigeria 16 KB 0 [71] 2012 Turkey 34 -94 [72] 2012 Nigeria 46 KB 20 [73] 2012 Spain 204 KB 99 [74] 2012 India 135 KB 94 [75] 2012 Brazil 1998 (Y): 48 KB 4 [76] 2008 (Y): 56 70 2012 USA 270 -100 [77] 2012 China 163 CA -85 [78] 77 HA 87 † All the strains belonged to a single clone. ‡…”
Section: Enterobacter Sppmentioning
confidence: 99%